2015
DOI: 10.1039/c4fo00529e
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-coated: exopolysaccharide producing lactic acid bacteria for food and human health applications

Abstract: The human enteric microbiome represents a veritable organ relied upon by the host for a range of metabolic and homeostatic functions. Through the production of metabolites such as short chain fatty acids (SCFA), folate, vitamins B and K, lactic acid, bacteriocins, peroxides and exopolysaccharides, the bacteria of the gut microbiome provide nutritional components for colonocytes, liver and muscle cells, competitively exclude potential pathogenic organisms and modulate the hosts immune system. Due to the extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
140
1
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 180 publications
(176 reference statements)
1
140
1
10
Order By: Relevance
“…Among the most studied probiotics, lactic acid bacteria (LAB) possess a cell wall that is typically composed of a thick peptidoglycan layer decorated with proteins, teichoic acids, and polysaccharides (19), which can act as microbe-associated molecular patterns (MAMPs). EPSs, apart from their technological properties and industrial applications, have been found to contribute to several health-promoting features of probiotics, such as antitumor, antiulcer, immunomodulatory, antiviral, and cholesterol-lowering activities (20,21), but their mechanisms of action have not been clearly established and are probably diverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most studied probiotics, lactic acid bacteria (LAB) possess a cell wall that is typically composed of a thick peptidoglycan layer decorated with proteins, teichoic acids, and polysaccharides (19), which can act as microbe-associated molecular patterns (MAMPs). EPSs, apart from their technological properties and industrial applications, have been found to contribute to several health-promoting features of probiotics, such as antitumor, antiulcer, immunomodulatory, antiviral, and cholesterol-lowering activities (20,21), but their mechanisms of action have not been clearly established and are probably diverse and complex.…”
Section: Discussionmentioning
confidence: 99%
“…The HePS synthesis mechanism is more complicated. In this process, the precursor nucleotide units such as UDP-GalNac, GDP-fructose, dTDPrhamnose, UDP-galactose and UDP-glucose are synthesized intracellularly from glucose-1-phosphate and fructose-6-phosphate [22,26]. Additionally, several enzymes and/or proteins are involved in the biosynthesis and secretion of HePS.…”
Section: Biosynthesis Of Exopolysaccharides By Lactic Acid Bacteriamentioning
confidence: 99%
“…The majority of EPSs produced by LAB are HePS, containing three to eight repeating units composed of two or more monosaccharides ( Figure 1) [22]. The HePS are produced by a great variety of mesophilic and thermophilic LAB.…”
Section: Hetero-exopolysaccharidesmentioning
confidence: 99%
“…the extracellular glucosyltransferase or fructosyltransferase (GT) dependent pathway, and the Wzy/Wzx-dependent pathway (Ryan et al 2015). The substrate used for the synthesis of homopolysaccharides via the GT dependent pathway is sucrose or another oligosaccharide containing fructose for fructan synthesis (Galle and Arendt, 2014), and the energy used in this process derives from its hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many different types of GT are encoded in the genomes of lactobacilli and only a small part of them have been biochemically characterized (van Hijum et al 2006). The GT pathway is a relatively simple enzymatic process, which requires low energy inputs (Ryan et al 2015).…”
Section: Introductionmentioning
confidence: 99%